Studies of injection parameters for chemical flooding in carbonate reservoirs. (August 2017) - Bai, Mingxing; Zhang, Zhichao; Cui, Xiaona; Song, Kaoping
Abstract: Exploration for oil and gas in sandstone reservoirs is becoming more and more difficult, so people are shifting attention from traditional sandstone reservoirs to carbonate reservoirs which are widely distributed around the world. This paper reviews different EOR technologies for carbonate reservoirs such as chemical flooding, air injection and some other methods. Secondly, with regard to chemical flooding, polymer flooding, surfactant flooding and their combination have been discussed in terms of their applications. Thirdly, the optimization of injection parameters using numerical simulation technique has been discussed and demonstrated taking a carbonate oilfield in Russia as an example. Chemical flooding is an attractive approach to explore fractured carbonate reservoirs, and surfactant/polymer flooding is the most efficient due to its synergetic effects of interfacial tension (IFT) reduction and mobility control with minimal side effects. A numerical simulation technique has been used to demonstrate the process of optimizing injection parameters for surfactant/polymer flooding in the carbonate reservoirs. The technique is different from that for sandstone reservoirs because it takes the effects of wettability, interfacial tension, capillary forces, and fracture parameters into consideration. Different scenarios are simulated to optimize the injection parameters, such as molecular weight and concentration, injection rate and volume, etc. The results are analyzed using variance analysis. It is found that for the pilot area, the best scenario is obtained with polymer molecular weight of 20 million, polymer concentration of 1000 mg/L, surfactant mass fraction of 0.1%, injection rate of 0.02 PV/a, and slug size of 0.3 PV. Similar approaches can be used to optimize the injection parameters in similar carbonate reservoirs.